Technological Trends in Natural User Interfaces - Tashev, Ivan ("Human-Computer Interaction: Present and Future Trends", P Montuschi, A Sanna, F Lamberti, and G Paravati, eds., 2014)
Industry Perspective video about the trends in NUIs with a special focus on intelligent audio interfaces that can identify speakers and adapt interactions between humans and machines.
P Montuschi, A Sanna, F Lamberti, and G Paravati, "Human-Computer Interaction: Present and Future Trends," Computing Now, vol. 7, no. 9, September 2014, IEEE Computer Society [online]; http://www.computer.org/portal/web/computingnow/archive/september2014.